**Answer:**

-3 = -2

**Step-by-step explanation:**

3 (x + 1) - 6 = 5x - 2 (1 + x)

3x + 3 - 6 = 5x - 2 - 2x

3x - 3 = 5x - 2 - 2x

3x - 3 = 3x - 2

= **-3 = -2**

**Answer:**

You add all these numbers then, divide the answer with 2.

**Step-by-step explanation:**

Trust

**Answer:**

**Step-by-step explanation:**

The formula of a circumference of a circle:

r - radius

We have r = 9in. Substitute:

1440 mi/do

The other three are stating a mileage per time period , this one does not

**Answer:**

1/12

**Step-by-step explanation:**

Let’s list out cases:

1+1:

Probability of getting 1 and 1 is (1/6)^2 = 1/36

1+2:

Probabilty of getting 1 and 2 is (1/6)^2 = 1/36 and getting 2 and 1 is (1/6)^2 = 1/36.

That is all of the cases because 1+3 and 2+2 are equal to 4. Summing it up, we get: 3(1/36) = 1/12